2003
DOI: 10.1007/s00467-003-1073-9
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular structural factors in progression of congenital nephrotic syndrome

Abstract: The glomerular structural factors associated with progression of congenital nephrotic syndrome of Finnish type (CNF) are incompletely understood. We studied glomerular volume and the proportion of various glomerular subtypes in seven CNF patients (aged 4 months to 3 years). Glomerular tubular connections (GTC) were analyzed in two patients early and late in the disease spectrum (creatinine 0.2 and 2.8 mg/dl, respectively). The proportions of "normal" glomeruli decreased (r=-0.91, P=0.003) and microcystic glome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…The most constant glomerular finding was mesangial sclerosis as reported previously. 13,14 Accumulation of extracellular matrix proteins and cells in the mesangium was evident in practically every glomerulus. Immunohistochemistry revealed that the glomerular tuft contained low numbers of inflammatory cells, indicating that the increased cellularity was caused by reactive mesangial cells.…”
Section: Discussionmentioning
confidence: 99%
“…The most constant glomerular finding was mesangial sclerosis as reported previously. 13,14 Accumulation of extracellular matrix proteins and cells in the mesangium was evident in practically every glomerulus. Immunohistochemistry revealed that the glomerular tuft contained low numbers of inflammatory cells, indicating that the increased cellularity was caused by reactive mesangial cells.…”
Section: Discussionmentioning
confidence: 99%